Analysis Of Factors That Determine Continuance Intention In Using Shopee Application During The Pandemic Covid-19 - Indrawati Indrawati; Nabila Ayu Shaina (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
The Covid-19 pandemic has made people spend more time in the digital space for work, communicating, shopping, or just looking for entertainment. Many people end up shopping from home using e-commerce to buy their daily needs. Shopee is one of the e-commerce sites in Indonesia that has won first place with the most visits and the number of transactions has continued to increase, especially during the Covid-19 period. This shows that there has been a change in user interest in adopting the Shopee application. This study aims to analyze the factors that influence Continuance Intention in using the Shopee application. The theoretical approach used in this study is the UTAUT 2 model because the research model has the strongest predictive value. The research data collection was carried out by distributing online questionnaires via Google Form to 400 respondents. This study was tested with PLS-SEM as a technique for analyzing 8 research constructs from the modified UTAUT2 model. The results showed that the factors that influenced the Continuance Intention in adopting the Shopee application from the highest to the lowest were Social Influence, Hedonic Motivation, Habit, Trust, and Performance Expectancy. This model is proven to strongly predict the desire of consumers to continue to adopt the Shopee application in the future because the R² in the study is 74.1%. The influence of the age moderating variable in this study does not affect the Continuance Intention of consumers in adopting the Shopee application. While the influence of the moderating variable gender affects the Trust variable on Continuance Intention.